You are on page 1of 76

# 2011.11.

14

()

, ()

C0

,
,

, C0
,
,()
,

,
, (, ),
, ,

C0
.Lagrange
1.nn-1Lagrange
( 1 )( 2 )...( i 1 )( i + 1 )...( n ) n
( k )
l i( n 1 ) ( ) =
( i 1 )( i 2 )...( i i 1 )( i i + 1 )...( i n )
=
k =1 (i k )
ki

1)i,2)ii,3)
( n1 )
l i ( ) n-1 i=1,2n
C0
2. l i( n 1 ) ( ) i=1,2n

1) n-1,n

1 i= j
2) l i( n 1 ) ( j ) = ij
0 i j

3)
i =1
l i( n 1 ) ( ) = 1
C0

3.
a. Lagrange (n=2)

( 2 ) 1 1
l ( ) =
1
= (1 ) = (1 + 1 )
(1 2 ) 2
1
2

( 1 ) 1 1
l ( ) =
1
= (1 + ) = (1 + 2 )
( 2 1 ) 2
2
2

li1 ( ) = 1 (1 + i )
2
C0

1
l ( ) = (1 + i )
1
i
2

1
l ( ) = 2 (1 )
1
1

1
l 21 ( ) = (1 + )
2
C0

b. Lagrange(n=3)

( 2 )( 3 ) 1 1
l12 ( )= = ( 1 ) = 1 ( 1 + 1 )
( 1 2 )( 1 3 ) 2 2

l 22 ( ) = ( 1 2 )

1 1
l 32 ( ) = ( 1 + ) = 3 ( 1 + 3 )
2 2
C0
Lagrange
n f j ( )
Ni = ln 1
( ) =
f j (i )
i
j =1, j i

f j ( ) = j f j ( j ) = j j = 0

f j ( i ) = i j

n n
= N i ( )i = lin 1 ( )i
i =1 i =1
3.2.2 Hermite
,
.
Hermite.
, Hermite
2 2

( ) = H i ( ) i + H i ( )
( )
0 (1)

i =1 i =1 i
4
( ) = H i ( ) Qi
i =1

Hermite
H ( j ) = ij ,
0 dH i0 ( )
j =0
i
d

H ( j ) = 0,
1 dH i1 ( )
j = ij
i
d
1=0, 2=1, i
H 0
( ) i ( )
H 1

1.0
H10 H 20

H11
1

1
1.0
H 21

N1 = H1(
0)
( )
= 1 3 2
+ 2 3

N 2 = H 2 ( ) = 3 2 2 3
( 0)

N 3 = H1 ( ) = 2 2 + 3
(1)

N 4 = H 2 ( ) = 2 + 3
(1)

Q1 = 1 , Q2 = 2 , Q3 = , Q4 =
1 2

Hermite Hermite .0 Hermite
Lagrange . ,
n Hermite n
Hermite. 2,2n+1.
2Hermite
2 2
d 2
d 2

( ) = H i ( )i + H i ( ) + H i ( ) 2
( 0) (1) ( 2)
i =1 i =1 d i i =1 d i

6
( ) = H i ( ) Qi
i =1

N1 = H1 ( 0)
( ) = 1 10 3 + 15 4 6 5 , Q1 = 1
N2 = H 2 ( 0)
( ) = 10 3 15 4 + 6 5 , Q2 = 2
d
N 3 = H1 ( ) = 6 + 8 3 , Q3 =
(1) 3 4 5

d 1
d
N 4 = H 2 ( ) = 4 + 7 3 , Q4 =
(1) 3 4 5

d 2
d 2
N 5 = H1 ( ) = ( 3 + 3 ) , Q5 = 2
( 2) 1 2 3 4 5

2 d 1
2

( )
2 1 3 4
(
N 6 = H 2 ( ) = 2 + , Q6 = 2
5 d
)
2 d 2

,
(),.
3,: i
A
Li=Ai/A
Ai

: Ni=Li
ijm
Px, y

Ai Aj Am
Li = Lj = Lm =
A A A

A iA jA m P
jmPmiPij
LiL jL mP
1
Pjm
1 x y
1
Ai = 1 x j y j = ( ai + bi x + ci y )
2
1 xm ym
1
Li = (ai + bi x + ci y ) (i, j , m)
2A
3xixjxm

aibici xi Li + x j L j + x m Lm = x

y i li + x j L j + x m Lm = y
1.
,
f j( ) ( L1 , L2 , L3 )
i
2 i
Ni = (i )
j =1 f j ( L1i , L2 i , L3i ) A
, ( L , L , L ) i
f ()
j
i
1 2 3
Ai
f ( L , L , L ) = 0 ()
j
i
1 2 3

.,i=1, f ( ) j
1

4,6 f1(1) ( L1 , L2 , L3 ) = L1 1 2 = 0
3
2,5,3
(L , L , L ) = L = 0
f2
() 1
1 2 3 (,0,)
1
(0,, )
. 6 5
4
1 2
(, ,0)
f j(i ) ( L1i , L2i , L3i )ij
(),
L1 = 0
:
3

L1 1
2 L1
(,0,) (0,, )
N1 = = ( 2 L1 1) L1
6 5
1
2 1 1 4 2
(, ,0)
1
L1 =0
2
, :
L2 12 L2
N2 = = ( 2 L2 1) L2
1
2 1
L3 1 2 L3
N3 = = ( 2 L3 1) L3
1
2 1 3
L1 L2 (,0,) (0,, )
N 4 = = 4 L1 L2 6 5
1 1
2 2
1 4 2
L2 L3
N5 = = 4 L2 L3 (, ,0)
1 1
2 2

L3 L1
N 6 = = 4 L1 L3
1 1
2 2
2

: Ni = Li (2 Li 1)(i, j , m)

: Ni = 4 L j Lm (i, j , m; i, j , m)

i10

i : A i = A A j = A m = 0

Li = 1L j = Lm = 0 Ai Aj Am
Li = Lj = Lm =
A A A

Ni = 1 N j = Nm = 0 N i = N j = N m = 0
: N i = Li ( 2 Li 1)(i, j, m )

: N i = 4 L j Lm (i , j , m ; i, j, m )

i : Ai = 0A j = Am = A / 2

Li = 0L j = Lm = 1 / 2
Ni ' = 1 N j ' = Nm' = 0 Ni = N j = N m = 0

3

## {PV } = A [ N ] {PV }hdxdy

e T

[ N ]212 = [ N i N j N m N i N j N m ]
a!b!c!
A i L j Lmdxdy =
a b c
L 2A
(a + b + c + 2)!
: N i = Li ( 2 Li 1)(i, j, m )

: N i = 4 L j Lm (i , j , m ; i, j, m )

hA
{ PV }e = [0 0 0 0 0 0 0 1 0 1 0 1]T
3
1/3

## {PS }e = [ N ]T {PS }hdl

l

ijxps

1
{PS } = Ps lh[1 0 1 0 0 0 0 0 0 0 4 0]T
e

4/61/6
ijxps
ips j0

Ps lh 1 2 T
{PS } =
e
[ 0 0 0 0 0 0 0 0]
2 3 3

2/3
1/3
2.

()

Li 2 3 Li 13 Li 1
Ni = = ( 3Li 2 ) Li (i=1,2,3,4)
1
3
2
3 1 2
3
4 (1/3,0,1/3) 8 7 (0,1/3, 2/3)
L1 L2 L1 1 3 9
N4 = = L1 L2 ( 3L1 1)
2 3 13 13 2
9 (1/3,1/3,1/3) 6
(2/3,0,1/3) 10 (0,2/3,1/3)

L1 L2 L3
N10 = = 27 L1 L2 L3 1 4 5 2
13 13 13 (2/3,1/3,0) (1/3,2/3,0)
.Lagrange
1.
n+1 n l In ( )
m+1 m l Jm ( )

1) N IJ = l n
I ( ) l J ( )
m

N IJ ( r , s ) = l I ( r )l J ( s ) = Ir Js
n m

n+ 1 m+1

I =1 J =1
N IJ ( , ) = 1

2).4
Lagrange
1
N i = ( 1 + i )( 1 + i ) i = 1,2 ,3 ,4
4

3). 9 ( 0 = i , 0 = i )

1
Ni ( ,) = 00 (1 + 0 )(1 + 0 ) i = 1,2,3,4
4
1
Ni ( ,) = 0 (1 + 0 )(1 2 ) , i = 5,7
2
1
Ni ( ,) = 0 (1 + 0 )(1 2 ) , i = 6,8
2

N9 ( ,) = (1 2 )(1 2 ) ,
2.Lagrange
1)Lagrange
2)
a) (n-1)(m-1)
0

b)

pnn=(p+1)2
4()
: 3, 75%
1, 25%
9()
: 6, 67%
3, 33%
16()
: 10, 62.5%
6, 37.5%

.Serendipity

Zienkiewicz

Lagrange

,
1.8
5
Lagrange
Lagrange
1
N5 = (1 + )(1 2 )
2
1
N 7 = (1 )(1 2 )
2 i=5,6,7,8
1
N 8 = (1 + )(1 2 )
2
1
N 6 = (1 )(1 2 )
2
N i ( j , j ) = ij i = 5 , 6 , 7 ,8
j = 1 , 2 , 3 ,..., 8
2)
1
N i = (1 + 0 )( 1 + 0 ) i = 1, 2 ,3 , 4 0 = i 0 = i
4
N i

a) N 1 ( 1 , 1 ) = 1

b) 0 i = 2 ,6 ,3 ,7 , 4
N 1 ( j , j ) = 1 }
2 j = 5 ,8

N i ( j , j ) = ij
1 1
N 1 ( , ) = N 1 N5 N8
2 2

N 2 ( , ) = N 2
1
N5
1
N 6
2 2

1 1
N 3 ( , ) = N 3 N 6 N 7
2 2

1 1
N 4 ( , ) = N 4 N 7 N8
2 2
:
(1)(1)
,
.
N 1 ( , ) = C ( 1 + )( 1 + )( + 1 )
1
Q N 1 ( 1 ) = 1, C =
4
1
( 1 + )( 1 + )( + 1 )
4

1 1
N 1 ( , ) = N 1 N5 N8
2 2
3)

a) N i ( j , j ) = ij
8 4
b) N i ( , ) =
i =1
N i ( , ) = 1
i =1
4)
1 , , , , 2
, 2
, 2
, 2

Lagrange
2 2

= 1, 1, , 2

= 1, 1, , 2

5
,()(
),
.

p,
(p,
p
.

.
:, 31
. ,
: N 5 ( , ) = A(1 B )(1 2 )(1 );
N 6 ( , ) = C (1 D )(1 2 )(1 ).
:
N5(-1/3,-1)=1, N5(1/3,-1)=0;
N6(-1/3,-1)=0, N6(1/3,-1)=1;
(-1,1) 4 (1,1)
: 3

A=9/32,B=3,C=9/32,D=-3

:
N 5 ( , ) = 9
32 (1 3 )(1 2 )(1 );
(-1/3,-1) (1/3,-1)
N 6 ( , ) = 9
32 (1 + 3 )(1 2 )(1 ). 1 5 6 2 (1,-1)
(-1,-1)

:

N1 = N 1 EN 5 FN 6 ; (1,1)
(-1,1) 4 3
N = N GN HN ;
2 2 5 6

:
1 (-1/3,-1) (1/3,-1)
N1 = (1 )(1 );
1 5 6 2 (1,-1)
4 (-1,-1)
1
N 2 = (1 + )(1 )

4
:
N1(-1/3,-1)=0, N1(1/3,-1)=0;
N2(-1/3,-1)=0, N2(1/3,-1)=0;
:
E=2/3, F=1/3, G=1/3, H=2/3
:
(-1,1) 4 (1,1)
3
2 1
N1 = N1 N 5 N 6 ;

3 3

1 2
N 2 = N 2 N5 N 6 ;

3 3
(-1/3,-1) (1/3,-1)
N 3 = N 3 ; 1 5 6 2 (1,-1)
(-1,-1)
N = N ;
4 4
1562,
(-1,1) 4 (1,1)
3

(-1/3,-1) (1/3,-1)
1 5 6 2 (1,-1)
(-1,-1)

N5 N6

2 1
N1 = N1 N 5 N 6 ;

3 3
:8,
571:
4 6 3

7

8

1 2
5
5:
N 5 ( , ) = 12 (1 2 )(1 ) 4 6 3

:N5(0,-1)=1, 7

N6()=0

8
7:
1 2
N 7 ( , ) = ( A + B )(1 )(1 )
2
5
:N7(-11/3)=1, N7(-1-1/3)=0;
:A=9/32,B=27/32
9
N 7 ( , ) = (1 + 3 )(1 2 )(1 )
32
1:
5-75-81
,
.
5-7 4 6 3
4
+ +1 = 0 7

3

5-8 8
2
+ +1 = 0 1 2
3
5
4 6 3
7

8
1: 1 2
5
2 4
N1 ( , ) = A( + + 1)( + + 1)(1 )(1 )
3 3

:N1(-1-1)=1,:A=9/32

1:

9 2 4
N1 ( , ) = ( + + 1)( + + 1)(1 )(1 )
32 3 3
. Serendipity

10

11

12

C0

()

K e

%

:
1
l ( ) = (1 + i ) = N i
1
i 1 1 i = 1, 2
2

1 1
N1 = N 1 N 3 N 2 = N 2 N 3 N 3 = 1 2
2 2

%
2 3
= N i i = H pa p
% i =1 % p =1

H = N 1
H2 = N 2 H3 = N3
1

1 + 2
a1 = 1 a2 = 2 a3 = 3
2

3 1 + 2
= H p a p = N 1 1 + N 2 2 + N 3 ( 3 + )
% p =1 2
H1 H2 H3

12

4
H ( ) = (1 2
)
H 4 ( ) = (1 2 )

= 1, H 4 (1) = (1 2 ) = 0

= 1, H 4 (1) = (1 2 ) = 0

= 0, H 4 (0) = (1 2 ) = 0

= 0, dH 4 ( )
= 1 2 = 1
d = 0
4
= H p a p
% p =1
d 1 + 2
a4 =
d = 0 2

1
( p 1)! ( p 1
1) ( p = 3,5,...)

H p ( ) =
1 ( p1 ) ( p = 4,6,...)
( p 1)!

d jHp 0 ( j = 2, 3,..., p 2)
=
d j =0 1 ( j = p 1)
d p1
ap = ( p 3) a p
d p1 = 0

C0